2001
DOI: 10.1080/00305364.2001.11745236
|View full text |Cite
|
Sign up to set email alerts
|

Functionally equivalent ages and hearing levels of children with cochlear implants measured with pre-recorded stimuli

Abstract: Three groups of children undertook an interactive computer-based closed-set test of the ability to identify pre-recorded spoken words presented acoustically. The test was completed by 31/39 children with profound hearing loss who had used the Nucleus Spectra-22 cochlear-implant system for at least one year (Group A); by 30 children with normal hearing (Group B); and by 22 children with severe-profound hearing loss who used acoustic hearing aids (Group C). Among the implanted children, those who were younger wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As early as 1994, Boothroyd and Eran (1994) proposed that children with cochlear implants functioned like children with hearing loss of 88 dB PTA who used hearing aids. Based on speech recognition results, other investigators have confirmed that many children using cochlear implants have a hearing level equivalent to those in the severe hearing loss range (Nakisa et al, 2001;Snik et al, 1997). Blamey et al (2001) concluded that children with implants and an average hearing loss of 106 dB HL performed on speech perception, production, and language measures such as children with hearing aids with an average hearing loss of 78 dB HL.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1994, Boothroyd and Eran (1994) proposed that children with cochlear implants functioned like children with hearing loss of 88 dB PTA who used hearing aids. Based on speech recognition results, other investigators have confirmed that many children using cochlear implants have a hearing level equivalent to those in the severe hearing loss range (Nakisa et al, 2001;Snik et al, 1997). Blamey et al (2001) concluded that children with implants and an average hearing loss of 106 dB HL performed on speech perception, production, and language measures such as children with hearing aids with an average hearing loss of 78 dB HL.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have summarised the results of comparisons between implanted and non-implanted children as a functionally-equivalent hearing level (Osberger et al, 1991;Osberger, Maso, & Sam, 1993;Boothroyd & Eran, 1994;Geers & Moog, 1994;Snik et al, 1997;Meyer et al, 1998;Svirsky & Meyer, 1999;Nakisa et al, 2001;Blamey et al, 2001). This is the unaided AHL of non-implanted children who achieve the same level of outcome as a child with an implant.…”
Section: Functionally-equivalent Equivalent and Significant Hearing mentioning
confidence: 99%
“…; Tait & Lutman, 1997); cross-sectional with crosssectional controls (e.g. Boothroyd & Eran, 1994;Nakisa et al, 2001); prospective with cross-sectional controls (e.g. Meyer et al, 1998;Osberger et al, 1991;Snik, Vermeulen, Brokx, Beijk, & van den Broek, 1997;Svirsky & Meyer, 1999); and prospective with prospective controls (e.g.…”
Section: Ethnicitymentioning
confidence: 99%